2011
DOI: 10.4049/jimmunol.1100499
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bacterial Resistance Mechanism against Human Group IIA-Secreted Phospholipase A2: Role of Streptococcus pyogenes Sortase A

Abstract: Human group IIA-secreted phospholipase A2 (sPLA2-IIA) is a bactericidal molecule important for the innate immune defense against Gram-positive bacteria. In this study, we analyzed its role in the host defense against Streptococcus pyogenes, a major human pathogen, and demonstrated that this bacterium has evolved a previously unidentified mechanism to resist killing by sPLA2-IIA. Analysis of a set of clinical isolates demonstrated that an ∼500-fold higher concentration of sPLA2-IIA was required to kill S. pyoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 59 publications
3
36
0
1
Order By: Relevance
“…We propose that PA colonization improves this elimination by increasing sPLA2-IIA expression of airways cells. In agreement, previous studies showed that sPLA2-IIA is present in human and animal biological fluids or cell supernatants at sufficient levels to kill bacteria 21,[53][54][55][56] . AMPs such as LL-37 have also been shown to play a role in pulmonary host defense toward SA and PA in CF lungs 57 , although the antimicrobial activity of these AMPs is impaired in CF airways [57][58][59] .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We propose that PA colonization improves this elimination by increasing sPLA2-IIA expression of airways cells. In agreement, previous studies showed that sPLA2-IIA is present in human and animal biological fluids or cell supernatants at sufficient levels to kill bacteria 21,[53][54][55][56] . AMPs such as LL-37 have also been shown to play a role in pulmonary host defense toward SA and PA in CF lungs 57 , although the antimicrobial activity of these AMPs is impaired in CF airways [57][58][59] .…”
Section: Discussionsupporting
confidence: 73%
“…NET289, NEN Radiochemicals, MA, USA). This allowed labelling of bacterial membrane phospholipids 55 . After centrifugation (3,000 g, 25°C, 15 min), bacterial pellets were suspended in 5 ml of LB medium and incubated for additional 30 min to allow binding oleic acid on the surface of bacteria to be incorporated, followed by rinsing once using 0.15 M NaCl to remove non-incorporated 3 H-OA.…”
Section: Methodsmentioning
confidence: 99%
“…Bacillus subtilis is among the most sensitive to sPLA 2 -IIA, with as little as 0.1–1 nM (1.5–15 ng/ml) of human sPLA 2 -IIA sufficient to produce 1–3 logs killing of 10 6 bacteria/ml within 1 hour of incubation. Similar effects on S. aureus and Streptococcus agalactiae (20) (Group B streptococci; GBS) generally (but see below) require 10–100× higher sPLA2-IIA concentrations. Other Gram-positive bacterial species (e.g., Staphylococcus epidermidis, Streptococcus pyogenes , Enterococcus faecalis ) can also be killed by sPLA 2 -IIA but require even higher (10–100-fold) doses (17, 20).…”
Section: Actions Of Purified Spla2-iia Against Gram-positive Bacteriamentioning
confidence: 87%
“…Up to 12 GAS cell wall-anchored proteins contain LPXTG-like motifs [6], such as M proteins, protein F, C5a peptidase (ScpA), protein G-related α2-macroglobin-binding protein (GRAB), and pili [7]. Mutation of SrtA in most human Gram-positive pathogens, including GAS, dramatically reduced their ability to infect animals [8][13]. Analysis of 24 isolates of 12 GAS serotypes indicates that SrtA is present in all strains examined [14], indicating that SrtA is highly conserved and for that reason is a potential target for vaccine candidate.…”
Section: Introductionmentioning
confidence: 99%